Reliability of spatial-temporal metrics used to assess collective behaviours in football: an in-silico experiment - Corsie, M.; Swinton, P. A. (Science and Medicine in Football, 2023)
Background: The purpose of this study was to investigate the reliability of spatio-temporal measurements applied within collective behaviour research in football. Methods: In silico experiments were conducted introducing positional errors (0.5, 2 and 4 m) representative of commercial tracking systems to match data from the 2020 European Championship qualifiers. Ratios of the natural variance (`signal`) of spatio-temporal metrics obtained throughout sections of each game relative to the variance created by positional errors (`noise`) were taken to calculate reliability. The effects of error magnitude and time of analysis (1, 5 and 15 mins; length of attack: <10, 10-20, >20 s) were assessed and compared using Cohen`s f2 effect size. Results: Error magnitude was found to exert greater influence on reliability (f2 = 0.15 to 0.81) compared with both standard time of analysis (f2 = 0.03 to 0.08) and length of attacks (f2 = 0.15 to 0.32). Discussion: The results demonstrate that technologies generating positional errors of 0.5 m or less should be expected to produce spatio-temporal metrics with high reliability. However, technologies that generate errors of 2 m or greater may produce unreliable values, particularly when analyses are conducted over discrete events such as attacks, which although critical, are often short in duration.